2017
DOI: 10.18054/pb.v119i1.4408
|View full text |Cite
|
Sign up to set email alerts
|

Growth and photosynthetic reactions of different species of wheat seedlings under drought and salt stress

Abstract: Background and Purpose: Comprehension of how the different representatives of the tribe

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 20 publications
5
15
0
Order By: Relevance
“…The concentration of NaCl had a negative effect on the chlorophyll content of wheat [16]). Results of the present study were in line with the findings of Terletskaya et al [17] who reported that the chlorophyll content of T. monococcum, T. polonicum, T. macha, T. aestivum decreased significantly (by 75-84%) under stress conditions. Salama et al [18] reported that high salinity level of (200 Mm NaCl) resulted in the swelling of membranes in chloroplasts of sensitive wheat cultivars while it had little effect in the tolerant ones.…”
Section: Neoxanthine Contents Under Different Concentrations Of Nacl supporting
confidence: 93%
“…The concentration of NaCl had a negative effect on the chlorophyll content of wheat [16]). Results of the present study were in line with the findings of Terletskaya et al [17] who reported that the chlorophyll content of T. monococcum, T. polonicum, T. macha, T. aestivum decreased significantly (by 75-84%) under stress conditions. Salama et al [18] reported that high salinity level of (200 Mm NaCl) resulted in the swelling of membranes in chloroplasts of sensitive wheat cultivars while it had little effect in the tolerant ones.…”
Section: Neoxanthine Contents Under Different Concentrations Of Nacl supporting
confidence: 93%
“…Previously obtained data on tetraploid forms anatomy and morphophysiology revealed high adaptability of them, in particular the species T. dicoccum, to drought and salt stress [17,18]. It is obvious that the study of alloplasmic lines derived from inter-species intersections of T. aestivum with drought-tolerant tetraploid species T. dicoccum may have both theoretical and practical interest.…”
Section: Introductionmentioning
confidence: 99%
“…In general, the reduction in Chl a/b ratio in a given species increases its ability to cope with the stress conditions. 32 Therefore, our results suggest that the S. exigua attack did not cause significant structural changes in the photosynthetic apparatus of tomato, while maize shows a greater adaptability at the beginning of the infestation. Supporting Chl a/b results in our study, carbohydrate content in infested tomato leaves did not decrease significantly under all the studied time periods and in maize, carbohydrate content significantly increased more than control at 2 h and 2 d indicating higher tolerance in maize compared to tomato.…”
Section: Discussionmentioning
confidence: 56%